Multi-Infection Patterns and Co-infection Preference of 27 Human Papillomavirus Types Among 137,943 Gynecological Outpatients Across China - Liao, Guangdong; Jiang, Xiyi; She, Bin; Tang, Huijuan; Wang, Zhongyong; Zhou, Hongrong; Ma, Yan; Xu, Weidong; Xu, Hongxing; Chen, Wen; Ji, Jianguang; Xi, Mingrong; et al. (Frontiers in Oncology, 2020)
Background: The epidemiological feature of human papillomavirus (HPV) infection is distinctive in China. We aimed to investigate the multi-infection patterns and co-infection preference of 27 HPV types among gynecological outpatients across China. Methods: Overall 137,943 gynecological outpatients were recruited from eight tertiary hospitals located in seven regions of China, between July 1st, 2014 and December 31st, 2016. The overall, region-specific, age-specific and type-specific prevalence of HPV infection were calculated, respectively. The pattern of HPV infection was also evaluated. Furthermore, rate ratio was calculated to evaluate the co-infection preference of any two HPV genotypes. Results: The overall prevalence of 27 HPVs’ [17 high-risk (hr)/10 low-risk (lr)] infection was 23.5%. The age-specific HPV prevalence showed a ‘U-shaped’ pattern. The most prevalent hrHPV genotypes were 16, 52 and 58. Multiple infections were detected in 25.8% of the HPV-positive women, in which dual infection was more prevalent. HPV 16/18 were likely to co-infected with HPV 31 but unlikely with HPV 52/58, i.e., the co-infection of HPV 16 with HPV 31 was high (3.5-fold), but low for HPV 58 (1.8-fold) and 52 (1.2-fold), while the co-infection of HPV 18 with HPV 31 was high (4.3-fold), but low for HPV 52 (1.9-fold) and 58 (1.7-fold). Conclusions: We found that a novel co-infection preference of HPV 16/18 with 31, 52 and 58, consistent with Australian study reporting a cross-protective efficacy of HPV 16/18 vaccine for HPV 31, but barely for HPV 52/58. Therefore, vaccines could also protect against HPV 52/58 are highly warranted in China.